Long-term high physical activity modulates event-related potential indices of inhibitory control in postmenopausal women - Chang Xu (PeerJ, 2019)
Background Inhibition processing is sensitive to aging, and an age-related decline in inhibition processing has been associated with an accelerated rate of progression to Alzheimer disease. Elderly women are two to three times more likely than age-matched men to have Alzheimer disease. Therefore, this study examined whether long-term high physical activity affects inhibitory processing, specifically among postmenopausal women. Methods In total, 251 candidates were screened using the Montreal Cognitive Assessment and the Raven’s Standard Progressive Matrices to assess their cognitive abilities and the International Physical Activity Questionnaire (Chinese version) to assess their physical activity levels. The participants were then grouped into either a long-term high physical activity group (defined as more than 3 days of high intensity activity per week and gross metabolic equivalent minutes (MET-minutes) higher than 1,500 MET-minutes/week or a gross MET higher than 3,000 MET-minutes/week obtained through walking or other moderate or high intensity activity) or a control group and matched for demographic and health characteristics as well as cognitive scores. Event-related potentials (ERPs) were recorded as participants performed a Go/No-go task to assess inhibition processing. Results The long-term high physical activity group (n = 30) had faster Go reaction times than the control group (n = 30), whereas no significant difference between the two groups was found in their performance accuracy on the No-go task. For the ERP results, the latency of N2 component was significantly shorter in the long-term high physical activity group than that in the control group. Discussion The results of this study suggested that long-term high physical activity may increase the efficiency of the inhibitory control system by increasing the activity of response monitoring processes.